Kinovea-Based : Tennis Spin Serve Analysis - Aprilo, Ians; Asmawi, Moch.; Tangkudung, James (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2022)
Abstract ____________________________________________________________________ The purpose of this research is to describe the mastery level pattern of movement spin service in lawn tennis using kinovea motion analysis tools. Spin serves are chosen to be analyzed because this type of spin service is still difficult for some tennis players. while more and more service masters will have a chance of winning the match. This study used a sample of professional tennis athletes aged 14-16 years and the sampling technique used is purposive sampling. The descriptive method is used in this study and the data analysis technique used is descriptive statistics. the procedure of this research, the sample performs a spin service, and a video is recorded, then analyzed using the kinovea motion analysis application. Analytical guidelines refer to instrument assessment of the movement patterns of the lawn tennis spin service. The results showed that 34% of tennis athletes belonged to the high category, 58% classified as moderate category, and 8% classified as low category, while the mastery rate of each stage of the spin service pattern was obtained low category at the ball toss stage 44%, medium category at coiling stage 54%, backswing 71%, uncoiling 61%, strike zone 71%, and fall in 83%. The follow-through stage got the highest category of 92%. A single paragraph of 200 to 300 words. The abstract should not contain any undefined abbreviations or unspecified references.